Adaptation of Organizational Social Entrepreneurship Scale into Turkish: Validity and Reliability Study - Ömer İşcan; Şahin Gafuroğlu (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This study aimed to adapt the "Organizational Social Entrepreneurship" scale to Turkish and to examine its psychometric properties. Following this purpose; It was tried to examine how accurately the scale measures (validity) and how consistent it is when measuring the structure (reliability). Within the scope of validity examinations, explanatory factor analysis was applied to the scale and then the suitability of the model was tested with confirmatory factor analysis. In the second step of the psychometric evaluation, the reliability evaluation was provided with the Cronbach Alpha coefficient, also known as the internal consistency coefficient. In the study, a questionnaire developed for the scale was applied to 305 employees working in various departments of Gaziantep Metropolitan Municipality. In the final evaluation, the scale is in the form of a 6-dimensional and 20-item structure according to the explanatory factor analysis. The total explained variance rate of the scale was calculated as 80.964% and the internal consistency (Cronbach's Alpha) coefficient was calculated as α= 0.946. After the factors were determined by explanatory factor analysis, they were tested with confirmatory factor analysis to test their suitability for factor structures, and all factors were found to be statistically significant. As a result, the findings on the psychometric properties of the Organizational Social Entrepreneurship scale, which was adapted into Turkish, reveal that it can be applied as a reliable and valid tool in studies on social entrepreneurship activities of organizations.